(untitled) - Emery, James C. (New York, 1987)
Information has been a scarce commodity in most of human history. All that has changed--but most businesses don't know how to make the most of it. Most organizations use their management information systems only to handle routine transactions like payroll and billing. This book shows executives how a management information system can provide help at all levels: operational, where the work gets done, as well as tactical and strategic, where planning and policy are determined.
Keywords: Management information systems,Hệ thống thông tin quản lý